2014
DOI: 10.3109/14756366.2014.951349
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the inosine 5′-monophosphate dehydrogenase (IMPDH) inhibitors

Abstract: Inosine 50 -monophosphate dehydrogenase (IMPDH) is important molecular target for potential anticancer, antiviral, antibacterial and immunosuppressive agents. A lot of compounds were obtained to establish their activity toward this enzyme, and to improve therapeutic properties of IMPDH inhibitors used as the drugs. Some of the recently reported analogs exhibited promising results during in vitro and in vivo examinations in comparison to substances applied in clinic. In this review, we describe synthesis and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Mycophenolic acid inhibits IMPDH, acting analogously to ribavirin to deplete GTP pools. In contrast, brequinar is a compound that acts by inhibiting dihydroorotate dehydrogenase, a key enzyme in pyrimidine synthesis, depleting both CTP and TTP ( 38 , 39 ). By treating cells during viral infection with each compound, we found that the high-fidelity nsP2 variant and double mutant were more resistant to both nucleotide-depleting compounds ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mycophenolic acid inhibits IMPDH, acting analogously to ribavirin to deplete GTP pools. In contrast, brequinar is a compound that acts by inhibiting dihydroorotate dehydrogenase, a key enzyme in pyrimidine synthesis, depleting both CTP and TTP ( 38 , 39 ). By treating cells during viral infection with each compound, we found that the high-fidelity nsP2 variant and double mutant were more resistant to both nucleotide-depleting compounds ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MPA 1 is a competitive and reversible inhibitor of inosine-5 0 -monophosphate dehydrogenase (IMPDH), predominantly isoforms II, which is present in tumor cells and in activated lymphocytes [7,8]. MPA 1 is an active substance of immunosuppressive drugs for the prevention of acute and chronic rejection of allogenic organ transplants.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to address this issue, significant efforts were focused on bioisosteric replacements along with various structural modifications of 1 to develop potent IMPDH inhibitors, but with limited success 12 , 25 . The MPA has proven to be an effective inducer of differentiation in a number of cancer cell lines (melanoma, leukaemia and prostate cancer).…”
Section: Introductionmentioning
confidence: 99%